Catastrophes and Lesser Calamities : the causes of mass extinctions. - Hallam, Tony (OUP Oxford, 2005)
Renowned geologist Tony Hallam takes us on a tour of the Earth's history, and of the cataclysmic events, as well as the more gradual extinctions, that have punctuated life on Earth throughout the past 500 million years.